2019
DOI: 10.30743/ll.v3i1.1998
|View full text |Cite
|
Sign up to set email alerts
|

Hate Speech Acts: A Case in Batu Bara

Abstract: Hate speech acts that occur in the online realm expressed with words of prejudice and negative feelings are far more dangerous than in the offline realm. Hate speech is a new area in the study of illocutionary speech acts. This new area of speech acts becomes more interesting because every hate speech has various meanings or illocutionary forces based on speaker’s intention. This study aims to analyse the classifications and aims of illocutionary acts and illocutionary forces of hate speech contained in two fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Ningrum (2018) also supports the results of this study through the results of her analysis regarding the form of hate speech on social media and the results in the finding that 32.63% of assertive illocutionary speech acts or the second most are forms of hate speech. It has supported by Rangkuti, et al (2019) Hate Speech Form of Expressive Speech -Insult Total = 1 utterances 0.3 % the thirteen hate speeches analyzed were assertive speech acts then directive (two utterances) and expressive (one utterance). The assertive speech acts in the study were in the form of statements and predictions.…”
Section: Hate Speech Forms Expressive Speech -Insultmentioning
confidence: 87%
“…Ningrum (2018) also supports the results of this study through the results of her analysis regarding the form of hate speech on social media and the results in the finding that 32.63% of assertive illocutionary speech acts or the second most are forms of hate speech. It has supported by Rangkuti, et al (2019) Hate Speech Form of Expressive Speech -Insult Total = 1 utterances 0.3 % the thirteen hate speeches analyzed were assertive speech acts then directive (two utterances) and expressive (one utterance). The assertive speech acts in the study were in the form of statements and predictions.…”
Section: Hate Speech Forms Expressive Speech -Insultmentioning
confidence: 87%
“…However, a study examining pejorative items indicating hate speech has still to be done. They checked propositional content, preparatory, sincerity and essential of the utterance to determine types of speech acts (Rangkuti et al, 2019). Alfina et al (2018) employed a machine-learning approach to detect hate speech in texts of Twitter data.…”
Section: Introductionmentioning
confidence: 99%
“…Alfina et al (2018) employed a machine-learning approach to detect hate speech in texts of Twitter data. Winiasih (2010) and Rangkuti et al (2019) studied hate speech using a linguistic approach. The former identified the use and function of Surabaya's swearing words using sociolinguistic theory; she has listed the swearing form and meaning (Winiasih, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some previous researchers conducted the same research that the topic is about hate expression with a different focus. Hamnö (2019), Subyantoro & Siroj (2019), Rangkuti et al (2019), andWiana (2019) have researched hate speech in social media on political scope. Sari et al (2019), Hafisa & Hanidar (2020, and Kadhum (2021) observed hate speech that was viewed from an impoliteness strategy perspective that was found in movies.…”
Section: Introductionmentioning
confidence: 99%